PENINGKATAN KEMAMPUAN BERBICARA MELALUI TELEPON DENGAN METODE BERMAIN PERAN DI KELAS IV SDN 1 TEUBENG - Nanda Saputra (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2017)
The purpose of this research is to improve students' speaking ability over the phone by using role-playing method in the 4th grade of SD Negeri 1 Teubeng. The subjects in this research were all 32 fourth grade students. This research is classroom action research (CAR). The data collection techniques used are observation sheets, tests, and documentation. From the results of the first cycle of action research, the average student score was 67.5% with classical learning completion of 68.75%, then in the second cycle, the average score increased to 76.04% with classical completion of 87.5%. Therefore, it can be concluded that through the role-playing method, fourth grade students of SD Negeri 1 Teubeng can improve their speaking ability over the phone in learning Indonesian.